Polycaprolactone/gelatin electrospun nanofibres containing biologically produced tellurium nanoparticles as a potential wound dressing scaffold: Physicochemical, mechanical, and biological characterisation - Mohsen Doostmohammadi; Hamid Forootanfar; Mojtaba Shakibaie; Masoud Torkzadeh‐Mahani; Hamid‐Reza Rahimi; Elham Jafari; Atefeh Ameri; Alieh Ameri (IET Nanobiotechnology)
Abstract The biologically synthesised tellurium nanoparticles (Te NPs) were applied in the fabrication of Te NP‐embedded polycaprolactone/gelatin (PCL/GEL) electrospun nanofibres and their antioxidant and in vivo wound healing properties were determined. The as‐synthesised nanofibres were characterised using scanning electron microscopy (SEM), energy‐dispersive X‐ray (EDX) spectroscopy and elemental mapping, thermogravimetric analysis (TGA), and Fourier‐transform infrared (FTIR) spectroscopy. The mechanical properties and surface hydrophobicity of scaffolds were investigated using tensile analysis and contact angle tests, respectively. The biocompatibility of the produced scaffolds on mouse embryonic fibroblast cells (3T3) was evaluated using MTT assay. The highest wound healing activity (score 15/19) was achieved for scaffolds containing Te NPs. The wounds treated with PCL/GEL/Te NPs had inflammation state equal to the positive control. Also, the mentioned scaffold represented positive effects on collagen formation and collagen fibre's horizontalisation in a dose‐dependent manner. The antioxidative potency of Te NP‐containing scaffolds was demonstrated with lower levels of malondialdehyde (MDA) and catalase (∼3 times) and a higher level of glutathione (GSH) (∼2 times) in PCL/GEL/Te NP‐treated samples than the negative control. The obtained results strongly demonstrated the healing activity of the produced nanofibres, and it can be inferred that scaffolds containing Te NPs are suitable for wound dressing.